Asia middle income challenge an overview. - Estrada, Gemma Esther B. (Economics working papers., 2017)
Developing Asia has undergone a relatively rapid transformation from a region that consisted mainly of low income economies toward one that is largely middle income. A key challenge for the region is sustaining rapid growth to move further to high income. The experience of newly industrializing economies shows that innovation, human capital, and infrastructure are critical to enabling a quicker shift to high income.